Masyumi’s Campaign Strategies in the 1955 Election in Jakarta - Ajeng Kusuma Ayu; Singgih Tri Sulistiyono; A. Alamsyah (Diponegoro University, 2020)
In the capital’s 1955 election, Masyumi established itself a place among the winning parties with 167,707 votes, surpassing their biggest rivals PNI, PKI, and NU in parliamentary votes. Nevertheless, it was not an easy victory. This study questions on why Masyumi was able to win the capital’s 1955 election and made PNI failed to gain the upper hand in Jakarta, despite the region being politically heterogeneous and thus theoretically an easy territory to conquer by the nationalists. By using the historical method, this study answers the above questions. The result of this study is a fact that the race between Masyumi and PNI to gain votes was one of a riveting story. As the center of power where major political, social, and economic activities were conducted, the political constellation in Jakarta was comparatively more dynamic to regions outside the capital. Hence, Masyumi’s triumph over the other major parties holds some historical significance. The fact that Masyumi triumphed over PNI (who were the winner on a national level) deserves a study unto itself, through which we can analyze Jakarta’s political composition at the time, the political strategies employed by competing parties, voters’ attitude, people’s political participation and furthermore, Masyumi’s campaign strategies.